Wound healing potential of Adenium socotranum (Vierh.) leaf extract: Phytochemical profiling and molecular docking analysis - Ibrahim Ali Al-Hakami, Bushra Abdulkarim Moharram, Hassan M. AL-Mahbashi, Tareq Al Maqtari, Wafa M. Al-Madhagi (Journal of Applied Pharmaceutical Science, 2025)
Adenium socotranum, a succulent plant endemic to Socotra Island, Yemen, is traditionally used to treat skin inflammation. This study aimed to identify the chemical constituents and evaluate the antioxidant, antimicrobial, and wound healing properties of the methanolic leaf extract of A. socotranum. Phytochemicals were investigated via gas chromatography-mass spectroscopy, while the antioxidant potential was determined using the 2,2-diphenyl-1-picrylhydrazyl assay. The antibacterial activity was determined using disc-diffusion and microdilution assays. For wound healing studies, the extract was topically applied to circular wound excisions in rats, followed by hydroxyproline content measurement and histopathological investigation. Molecular docking studies were conducted to identify potential molecular targets associated with the wound healing effects, specifically focusing on tumor necrosis factor-alpha (TNFα) and transforming growth factor-beta receptor 1 (TGF-βR1). The major compounds in the extract were methyl palmitate (35.22%), methyl stearate (22.21%), β-sitosterol (4.55%), and α-amyrin (5.49%). The extract exhibited a significant antioxidant effect (IC50 32.4 μg/ml). It showed a remarkable antibacterial effect on all tested bacterial species, particularly Enterococcus faecalis (minimum inhibitory concentration 13.7 μg/ml). Topical application of the extract at 20 mg/ml significantly (p < 0.001) promoted wound regeneration with wound healing percentages of 61.1% and 99.5% on days 3 and 12, respectively, compared to 34.4% and 93.1% in the control group. Additionally, the treatment significantly increased the hydroxyproline content to 81.2 μg/ml, compared to 33.3 μg/ml in the control. Extract-treated wounds contained fewer inflammatory cells, more blood capillaries, and denser collagen fibers. Among the identified phytoconstituents, α-tocospiro B, α-amyrin, and 1,2-benzenedicarboxylic acid exhibited notable binding affinities toward TNFα and TGF-βR1. The findings establish the wound healing potential of A. socotranum. α-tocospiro B, α-amyrin, and 1,2-benzenedicarboxylic acid are potential lead compounds responsible for the observed wound healing activity.
Keywords: A. socotranum, GC-MS, antioxidant, antibacterial, wound healing, molecular docking